Study of Nonlinear Deformation of FCC-AuCuSi under Pressure by the Statistical Moment Method. (5th March 2021) - Hoc, Nguyen Quang; Tinh, Bui Duc; Hien, Nguyen Duc; Coman, Gelu
Abstract : In this work, we build the model and derive the theory of nonlinear deformation for substitutional alloy AB with interstitial atom C and face-centered cubic structure under pressure from the statistical moment method. The calculation results for FCC-AuCuSi are presented. We obtain the values of density of deformation energy, maximum real stress, limit of elastic deformation, and the stress-strain curve and compare the calculated results with experiments and other calculations.